PENGEMBANGAN MEDIA BOARD GAME â€œPACAROLIâ€ PADA KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS I DI SD MUHAMMADIYAH AIMAS - Yolanda Mamonto, Tusi; Rahayu, Desti; Apia, Gika (Jurnal Lensa Pendas, 2025)
This study aims to develop a learning media in the form of a board game called "PACAROLI" to improve the early reading skills of first grade students at SD Muhammadiyah Aimas, Sorong Regency. This study uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The results of the study indicate that the "PACAROLI" board game media is valid, practical, and effective to be used as a learning media. The validity of the media is proven by the average score from the experts of 96%. Practicality is measured through student responses, with more than 70% of students giving positive responses. The effectiveness of the media is shown through the results of the pre-test and post-test which showed a significant increase (p <0.05). Thus, the "PACAROLI" media can be an innovative solution in improving the reading skills of first grade students. The researcher provides suggestions to several parties in the world of education. For students who often do playing activities, it is expected that they can increase their knowledge through learning activities while playing. For teachers, so that they can sort and utilize learning media that are in accordance with student characteristics and can foster student interest in learning. For the principal, to be able to consider the use of learning media that are in accordance with the characteristics of students and the demands of today's education. For further researchers, it is expected to be able to develop products from this research that are in accordance with the development of the times, and consider the feasibility, effectiveness, and practicality of the media for further research.